Perancangan Interior Rumah Robot di Surabaya - Yonathan Wicaksono S (Intra, 2013)
Surabaya is a city with a thriving cultural variety with a pluralistic society where people in Surabaya is more modern that easy to accept new things that developed in the community. The purpose of Interior Design of Robot House in Surabaya is to facilitate and develop the talents of children in Surabaya who have talent and a great interest in the field of robotics and introduce robots in more detail towards the children and also as a forum for developing robotic technology continue to thrive in the world, so that Indonesia was not always behind in the field of robotics.